ANALISIS CONTOH KONTEKSTUAL KONSEP MATEMATIKA SEKOLAH YANG TERDAPAT DALAM IBADAH SHALAT - Eri Agus Transyah; Dwi Astuti; Hamdani Hamdani (Universitas Tanjungpura, 2019)
AbstractThis research aim to know the examples of mathematic School concepts in in elementary school and junior school which included muslim prayer. The research methods were using study of literature. The references of this research are books and several documents that related to muslim prayer. The results of data analysis in this research was obtained examples of mathematic school concepts in muslim prayer in term of number theory, algebra and geometry. In term of number theory obtained part of addition whole number which included in rak'ah prayer, multiplication in prayer saying and double in rak'ah Tahajud prayer. In term of algebra obtained part of sets, empty set, set relation and set operation which included in muslim prayer and their rak'ah. Then obtained part of march pattern and arithmetics in which included in rak'ah witir and tahajud prayer. In term of geometry obtained part of line segment, parallel lines, 45 degree angle, 90 degree angle, and 180 degree angle which included in prayer movementsKeywords: Contextual examples, mathematics school concept, Shalat